PENGARUH LITERASI KEUANGAN, FINANCIAL ATTITUDE, LOKASI DAN RELIGIOSITAS TERHADAP MINAT MENABUNG DI BANK SYARIAH (Studi Kasus Pada Masyarakat Desa Sirap Juai Kab. Balangan) - Zakiyah; Abdul Wahab (Wahana Islamika Jurnal Studi Keislaman, 2022)
So far, financial institutions that have mushroomed to remote villages are still conventional banks as intermediaries for public finance transactions. Distance is an obstacle in efforts to access sharia-based banks located in Kota Regency. People often attend religious studies. The public may have understood the prohibition of conventional banks from using the practice of interest. Financial literacy can be obtained either from direct delivery in recitations or the media that are currently developing. If the level of a strong desire to use the services of Islamic banks by leaving the practice of haram (usury), then the financial attitude towards the location is not a significant reason to use Islamic banks. This study aims to determine the effect of financial literacy, financial attitude, location, and religiosity on interest in saving at Islamic banks in the people of Sirap Juai Village, Kab. Balangan. This study uses a quantitative-inferential research approach. The sample used was 77 people. While the research data were collected by distributing questionnaires to the people of Sirap Village. The data analysis technique used is multiple linear regression analysis. The results show that: 1) Partially the variables of financial literacy, financial attitude, location, and religiosity have a significant effect on interest in saving in Islamic banks. 2) There is a significant effect simultaneously (simultaneously) of the independent variable on the dependent variable.